Pentingnya Pencatatan Keuangan Dan Pencantuman Label Halal Produk Pada Home Industry Abon Ikan Tuna Segar G&R Masohi Shop Di Kelurahan Lesane Kecamatan Kota Masohi Kabupaten Maluku Tengah - Asrida, Wa; Hariyanti, Dwi; Astuti Musaid, Sri; Retno Hariyati, Tri (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2021)
This community service was performed at the home industry of G&R Masohi Shope in Lesane Village, Masohi City District, Central Maluku Regency. This devotional activity is carried out with the aim to: 1) provide understanding and assistance to partners